Alien foraminifers from Greek coastal areas (Aegean Sea, Eastern Mediterranean) - KOUKOUSIOURA, O.; DIMIZA, M.D.; TRIANTAPHYLLOU, M.V. (Mediterranean Marine Science, 2010)
The present study provides additional data on the distributional range of six alien foraminiferal species in living assemblages from Greek coastal areas (Aegean Sea, Eastern Mediterranean). Amphistegina lobiferaLARSEN 1976, Sorites orbiculus (FORSK L 1775) and Coscinospira hemprichii EHRENBERG 1839 are well established in Greek coastal areas, whereas Triloculina fichteliana D'ORBIGNY 1839, Planogypsina acervalis (BRADY 1884) and Cymbaloporetta plana (CUSHMAN 1924), are recorded for the first time in this paper. The occurrence of these species in a number of sites in the Aegean Sea establishes their presence in the Eastern Mediterranean.